Emotional Problems and its relationship with some personality features for some visual impaired pupils in Hama: An empirical study on a population of visual impaired pupils in inclusion schools in Hama Doctorate (Journal of Hama University, 2019)
This study aims at recognizing the emotional problems and its relationship with some personality features for visual impaired pupils in Hama. The population of study consists of (20) visual impaired pupils in public schools in first stage of basic learning. The study uses descriptive analytical approach by designing a questionnaire to measure emotional problems and another questionnaire to measure personality features for visual impaired pupils.The data have been analyzed using the statistical programme SPSS.The study finds that there is a significant statistical relationship between emotional problems and personality features for visual impaired pupils in all dimensions. The results are as follows:• There is a statistically significant relationship between anxiety and personality features (motivation, obedience, success expectation) for visual impaired pupils.• There is a statistically significant relationship between social violence and personality features (motivation, obedience, success expectation) for visual impaired pupils.There is a statistically significant relationship between hyperactivity and personality features (motivation, obedience, success expectation) for visual impaired pupils.